Sint-Denijs-City : Kunst langs trage wegen - Doutreluigne, Marc (s.l. : s.n.)
Burgos Labra, Fabiola ; Cafmeyer, Elias ; Chapman, Jake & Dinos ; Cop, Ilke ; Copers, Leo ; Danckaert, Bert ; Trans, D.D. ; de Cupere, Peter ; Delabie, Henk ; Delrue, Ronny ; Demeyer, Sofie ; Desal, Greet ; De Witte, Adelheid ; Dujardin, Filip ; Ervinck, Nick ; Gielis, Daan ; Kempenaers, Jan ; Kuilboer, Conny ; Martin, Kris ; Matloga, Neo ; Nicolodi, Renato ; Pfleiderer, Julie ; Philips, Karl ; Slangen, Nancy ; Puype, Peter ; Stragier, Stijn ; Van Canneyt, Nele ; Vanderschoot, Alice ; Van Heeschvelde, Kristof ; Vanmechelen, Koen ; Vansteenkiste, Jonas ; van Zadelhoff, Daniëlle ; Verheylesonne, Simon ; Verscheure, Klaus ; Vertessen, Liliane
Kunstbiennale Sint-Denijs-City, Zwevegem, 18 augustus - 24 september 2023.
boek